2022
DOI: 10.3389/fpubh.2022.1015166
|View full text |Cite
|
Sign up to set email alerts
|

Mapping network connection among symptoms of anxiety, depression, and sleep disturbance in Chinese high school students

Abstract: BackgroundDue to tremendous academic pressure, Chinese high school students suffer from severe depression, anxiety, and sleep disturbances. Moreover, senior high school students commonly face more serious mental health problems than junior high school students. However, the co-occurrence and internal relationships of depression, anxiety, and sleep disturbances clusters are scarcely examined among high students. Therefore, the current study inspected relationships between depression, anxiety, and sleep disturba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 64 publications
2
10
0
1
Order By: Relevance
“…Therefore, it can be considered as a transdiagnostic symptom and of greater anxious impact produced by the first months of mandatory quarantine in older adults (90), which is more closely linked to difficulty relaxing (A4; higher expected influence and anxiety/depression overlap) in the first network. These findings are in line with previous studies pointing to the interaction of such symptoms in the network (26,87), even in network outcomes where such symptoms are central (72,91).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, it can be considered as a transdiagnostic symptom and of greater anxious impact produced by the first months of mandatory quarantine in older adults (90), which is more closely linked to difficulty relaxing (A4; higher expected influence and anxiety/depression overlap) in the first network. These findings are in line with previous studies pointing to the interaction of such symptoms in the network (26,87), even in network outcomes where such symptoms are central (72,91).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it was evident that older adults who were assessed during the second wave were still experiencing a tendency to worry in an exaggerated way and with difficulties in controlling worry. The latter anxious symptom has also been previously reported as one of the most central among interacting systems of anxious and depressive symptomatology in young and older adults during the pandemic (65,(71)(72)(73).…”
Section: Discussionmentioning
confidence: 78%
“…The results of this study show that the symptoms of depression, sympathetic arousal, neurological, and cognitive disorganization in Chinese secondary school students are relatively obvious, which is basically consistent with the results of previous studies ( 22 , 35 , 36 ). Firstly, the depression symptoms in secondary school students are not depression in the clinical sense, but a kind of negative emotional experience characterized by persistent low mood.…”
Section: Discussionsupporting
confidence: 91%
“…Sixth, this study did not consider the impact of depression. In fact, depression was not only a significant predictor of sleep problems [104], but also an important factor that can influence people's emotional regulation and time usage [62,105]. Therefore, future research needs to take depression into account and examine the complicated interactions between depression, insomnia, emotion regulation, and time structure.…”
Section: Discussionmentioning
confidence: 99%
“…For example, an investigation of 111 participants conducted by Chang and Nguyen reported that the loss of time structure significantly predicted a decline in sleep quality [55]. Conversely, an experimental study of 114 women in China with perimenopausal syndrome revealed that the structured and purposeful use of time improves sleep quality and decreases insomnia symptoms [62]. Other studies reported that perceived stress and time structure were negatively correlated [5,63,64].…”
Section: Introductionmentioning
confidence: 99%